State-of-the-art nanotechnologies for the detection, recovery, analysis and elimination of liquid biopsy components in cancer. (February 2022) - Zhao, Mengnan; Mi, Dandan; Ferdows, Bijan Emiliano; Li, Yuke; Wang, Rujing; Li, Jiaojiao; Patel, Dylan; Kong, Na; Shi, Sanjun; Tao, Wei
Highlights: Potential blood-based biosources in cancer liquid biopsy were introduced. We reviewed nanoparticle-labeled with targeting-moieties, nanostructured substrates and nanobiosensors in liquid biopsy. The mechanisms and methods of using functional nanoparticles to capture and recover CTCs were summarized. Nanotechnology-mediated downstream analysis and elimination of CTCs were also discussed. We offered an outlook on the challenges and suggestions for nanotechnology-based cancer liquid biopsy. Graphical abstract: The applications of nanotechnology on the detection, recovery, analysis, and elimination of liquid biopsy components in cancer. ga1 Abstract: Liquid biopsy allows for the quick and noninvasive detection of tumor-associated components. Various liquid biopsy components, which include circulating tumor cells, tumor-derived extracellular vesicles, circulating tumor nucleic acids, and tumor-educated platelets, can be analyzed. These components hold great potential for tracking the evolutionary dynamics of tumors and detecting the early emergence of therapeutic resistance and tumor recurrence. In recent decades, significant advances in nanotechnology have contributed to the development of blood-based liquid biopsy with higher sensitivity and specificity. This review discusses the key nanotechnologies that can be used to detect, isolate, and recover tumor-associated components, providing a brief overview of the downstream analysis of these components and then focusing on the different types of nanomaterials that can be applied for the treatment of circulating tumor cells to prevent metastasis. Taken together, these noninvasive nanotechnology-mediated diagnostic approaches can aid precise cancer assessment and guide modifications to current treatment strategies.